Penerapan Metode Delta Modulation dalam Kompresi File Video Mp4 - Ita Nola (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of digital technology shows very rapid progress. This development is also closely related to the availability of the storage media needed for data storage. This need is due to the fact that more and more data is stored, and the size of the data is large. Compression is a technique to reduce the amount of data size from the original data. The general principle used in the video compression process is to reduce duplication of data in the video so that the memory needed to represent the original video. Many of the videos that are produced contain duplicate data. In this study, the authors applied the Delta Modulation method to perform MP4 videos. This method will compress by grouping pixels into 8x8 macro blocks. And added with the quantity process to shrink the pixel value, so that the Delta Modulation process works better on compressed MP4 videos.